Studies on Distant Hybridization Compatibility between the Azalea (Rhododendron × hybridum hort.) and the Rhododendron decorum Franch. Native to China - Ziyao Hao; Yefang Li; Yingying Yang; Jie Song; Jing Meng; Wenling Guan (Horticulturae, 2024)
Rhododendron resources are abundant in China, and hybridization breeding technology is the primary method for cultivating Rhododendron varieties. In order to optimize the utilization of wild Rhododendron resources for distant hybridization, this study took three horticultural varieties of Rhododendron subgenus Tsutsusi and the Rhododendron decorum Franch. of the subgenus Hymenanthes as the research objects, and the cross-compatibility between subgenera was analyzed from the aspects of pollen tube growth and ovary and seed development. At the same time, the statistics of ovary swelling rate and fruit bearing rate, numbers of capsule seeds, 1000 seed weight of hybrid seeds, germination rate, green seedling rate, and other indexes were analyzed to comprehensively evaluate hybrid fertility. The results showed that there was obvious pre-fertilization and post-fertilization barriers existing in the hybridization of Rhododendron × hybridum hort. and R. decorum. During the growth of pollen tubes, a large amount of callus appeared, which led to the entanglement, distortion, and abnormal development of the pollen tubes; only part of the pollen tubes entered into the ovary or ovule. The pre-fertilization barriers can be overcome by early pollination and delayed pollination. According to the observation of the ovary paraffin section, 45 d after pollination, the seed was shriveled and developed abnormally. The comprehensive evaluation of hybrid fertility showed that ‘Sima’ × R. decorum was fertile, ‘Yin Taohong’ × R. decorum was a weakly fertile, and ‘Little Taohong’ × R. decorum was sterile. This study provided a scientific basis for intergeneric hybridization breeding between the subgenus Tsutsusi and the subgenus Hymenanthes.